Is Homeopathic Arnica Effective for Postoperative Recovery? A Meta-analysis of Placebo-Controlled and Active Comparator Trials - Gaertner, Katharina; Baumgartner, Stephan; Walach, Harald (Frontiers in Surgery, 2021)
Background: Homeopathic Arnica montana is used in surgery, as prevention or treatment for reduction of pain and other sequelae of surgery. Our aim was to perform a meta-analysis of clinical trials to assess efficacy of Arnica montana to reduce the inflammatory response after surgery. Method: We conducted a systematic review and meta-analysis, following a predefined protocol, of all studies on the application of homeopathic Arnica montana in surgery. We included all randomized and non-randomized studies comparing homeopathic Arnica to placebo or to another, active comparator and calculated two quantitative meta-analyses and appropriate sensitivity analyses. We used “Hegde’s g”, an effect size estimator which is equivalent to a standardized mean difference corrected for small sample bias. The PROSPERO registration number is CRD42020131300. Results: 23 publications reported on 29 different comparisons. One study had to be excluded, because no data could be extracted, leaving 28 comparisons. Eighteen comparisons used placebo, 9 comparisons an active control, and in one case Arnica was compared to no treatment. The meta-analysis of the placebo-controlled trials yielded an overall effect size of Hedge’s g = 0.18 (95% confidence interval –0.007/0.373; p = 0.059). Active comparator trials yielded a highly heterogeneous significant effect size of g = 0.26. This is mainly due to the large effect size of non-randomized studies, which converges against zero in the randomized trials. Conclusion: Homeopathic Arnica has a small effect size over and against placebo in preventing excessive hematoma and other sequelae of surgeries. The effect is comparable to that of anti-inflammatory substances.